Optimization of the Simultaneous Determination of Sitagliptin and Metformin, in Human Plasma by A Rapid HPLC Method - Balamurugan K; Kirtimaya Mishra; Suresh R (Journal of Global Pharma Technology, 2019)
Simple, rapid and reproducible methods were established for quantitative determination of Sitagliptin (SIT) and Metformin (MET) spiked with plasma using an Onyx C18 Monolithic column  connected with an Onyx C18 guard cartridge.  and PDA detection at 210 nm. The mobile phase was MeOH, ACN, 0.01mM KH2PO4 (pH 3.5±0.5), adjusted with freshly prepared 10% orthophosphoric acid.  was pumped at 0.492 mL/min. The method was linear between 0.5-2.5 µg/mL, statistically validated for its linearity, precision and accuracy. The precision was found to be less than 1% showing high precision of the assay method. It was found that the excipients in the commercial tablet did not interfere with the method. Developed method can routinely use for the estimation of SIT and MET related compounds from the dosage form spiked with plasma.